Intravesical lidocaine decreases autonomic dysreflexia when administered prior to catheter change. (3rd September 2019) - Solinsky, Ryan; Linsenmeyer, Todd A.
Abstract : Objective: To evaluate the role of intravesical lidocaine in preventing autonomic dysreflexia (AD) during routine catheter changes in individuals with spinal cord injury (SCI) at T6 or above. Design: Prospective observational cohort study. Setting: Outpatient urology clinic. Participants: Fifty consecutive individuals with SCI at or above T6 and a history of AD having a routine indwelling catheter change. Interventions: A treatment group of individuals received 10 ml of 2% lidocaine administered into the existing catheter 4–6 minutes prior to catheter change. The control group had the same amount of lidocaine administered into the urethra or suprapubic tract after removing the old catheter and immediately prior to inserting the new catheter (due to the delayed onset of action of the anesthetic, this was assumed to have no initial effect). Systolic blood pressures (SBP) were measured immediately after catheter insertion and then every 30–45 seconds for 5 minutes. Outcome measures: Incidence and magnitude of AD as determined by SBP following catheter change. Results: The incidence of AD in the lidocaine treatment group was 14.8% vs 47.8% in the control group (P = .011). Pretreatment with lidocaine also demonstrated a significantly attenuated rise in SBP immediately after the catheter change (9.5 mmHg vs 26.9 mmHg for post-treatment, P = .014) relative to baseline SBP. Conclusion: In individuals with SCI at risk of AD, pretreatment with intravesical lidocaine prior to catheter change significantly decreased both the incidence and magnitude of AD. This suggests that pretreatment with intravesical lidocaine is helpful in individuals with SCI who are prone to AD.